Enhancing Experience-Based Cultural Walking Tours through the 4E Framework: A Case Study of Glodok (Chinatown), Jakarta - Latifah, Annisa Husnul; Kovalenko, Neswa; Vanit, Familia Dasil; Aliwarga, Glenn Richard; Kurnia, Mikha Eliazer (Ilomata International Journal of Social Science, 2025)
This study investigates how the Glodok Walking Tour can be optimized using the 4E Experience Framework—Entertainment, Education, Esthetics, Escapism—to enhance tourist involvement in cultural preservation. Although Jakarta is rich in heritage, tourism strategies often emphasize its modern image, resulting in the underutilization of areas like Glodok. As one of Southeast Asia’s oldest Chinatowns, Glodok offers cultural, and culinary attractions that align with contemporary tourists’ preferences for immersive experiences. While walking tours provide a sustainable platform for cultural engagement, existing designs often lack comprehensive experiential quality. This study seeks to address how the Glodok Walking Tour can be enhanced through the 4E framework to strengthen tourist involvement in heritage preservation. A qualitative case study was conducted, combining interviews with a tour guide and four tourists and participatory observation during the Glodok Walking Tour by Jakarta Good Guide. Data were analyzed using Miles and Huberman’s model, involving data reduction, thematic coding based on the 4E framework, and conclusion drawing. Triangulation ensured validity. Results Findings revealed gaps across all dimensions: weak interpretive techniques and lack of hands-on activities (Entertainment); information overload and limited contemporary relevance (Education); poor environmental conditions and insufficient engagement with landmarks (Esthetics); and restricted immersion due to noise and lack of local engagement (Escapism).Optimizing the Glodok Walking Tour through improved storytelling, multisensory learning, enhanced environmental quality, and direct engagement with local stakeholders can transform it into a more meaningful experience. These enhancements foster deeper emotional connections and contribute to the preservation of cultural heritage.